Bacillus velezensis LMY3-5 for the biocontrol of soft rot in kiwifruit: antifungal action and underlying mechanisms - Ren, Chunguang; Liu, Yu; Su, Wenwen; Tian, Bing (Frontiers in Microbiology, 2025)
Soft rot caused by Botryosphaeria dothidea is a serious fungal disease in kiwifruit observed during the storage period, and it seriously restricts the healthy and stable development of the kiwifruit industry. In the present study, the bacterial strain LMY3-5 with high antifungal activity was isolated from healthy kiwifruit tissues. Based on gyrA and 16S rRNA sequences, a phylogenetic tree was constructed, and LMY3-5 was identified as Bacillus velezensis. The 16% cell-free supernatant (CFS) of LMY3-5 suppressed B. dothidea spore germination and mycelial growth by 97.32%. The 16% CFS of LMY3-5 could effectively inhibit the expansion of kiwifruit soft rot in vitro, and the inhibition rate was 73.59%. The scanning electron microscopy (SEM) observations of B. dothidea mycelia treated with the 16% CFS for 12 h showed that the mycelia were curved, wrinkled, and sunken. Moreover, transmission electron microscopy (TEM) observations revealed blurred boundaries of mycelial cell walls as well as plasmolysis and vacuolization. Propidium iodide (PI) staining showed that the CFS treatment damaged the cell membrane of B. dothidea and affected its permeability, which led to leakage of the nucleic acids and proteins. Simultaneously, a substantial increase in the activity of key enzymes (i.e., β-1,3-glucanase and chitinase) was observed, which indicated damage to the cell wall function of B. dothidea. GC/LC–MS analysis revealed the presence of 27 antimicrobial compounds. Thus, the LMY3-5 strain showed great potential as a biocontrol agent for soft rot disease in kiwifruit.